(untitled) (Albayan Scientific Journal, 2023)
The research aimed to estimate the margins and marketing costs at farm level، wholesalers and retailers of vegetable crops (tomatoes - cucumbers - eggplant - dry onions) in the Al-Bayda municipality in Libya، and the study found that the marketing channels of vegetable crops pass through farmer to the wholesaler then to the retailer after that to the consumer، and the study relied on a questionnaire during the season of 2019-2020 and the marketing costs of tomatoes، cucumbers، eggplant and dry onions borne by the farmer were estimated 69.57، 288.96 ،296.24، 270.6 Dinar per tone respectively، as for the marketing costs borne by the wholesaler، they were by (66.42، 78.09، 64.28، 61.15) dinars per ton، respectively، while the marketing costs of retailer were estimated at (329.13، 295.62، 285.79 and 297.6) dinars per ton، respectively. The study of marketing differences is considered to be of great importance in order to find out the extent to which marketing efficiency is achieved and compare it with the production costs or prices that can be obtained. By studying the differences between the wholesaler and the farmer، it was found that they amounted to about 191.42 dinars per ton for the tomato crop، and about 238.09 dinars per ton for the cucumber crop، and about (214.28،216.15) dinars per ton for the eggplant and dry onion crops، respectively. As for the marketing differences between the retailer and the farmer، it amounted about (854.73،1139.44،738.06،763.3) dinars per ton for the crops of tomatoes، cucumbers، eggplant and dry onions، respectively، while the differences between the retailer and the wholesaler were estimated about (663.31،901.35،523.78،547.15) dinars per ton for tomato، cucumber، eggplant and dry onion crops، respectively، as well. The share of the farmer، the wholesaler، and the retailer of the consumer’s dinars amounted about (57.3%، 19.5%، and 33.2%) for the tomato crop respectively، and this share was about (62%، 8%، and 30%) for the cucumber crop، respectively، and about ( 75.4%، 7.1%، and 17.5% for eggplant crops، respectively، and finally (61.8%، 10.8% and 27.4%) for dry onion crops، respectively.